Sources of Muslim democracy: the supply and demand of religious policies in the Muslim world. Issue 1 (2nd January 2018) - Driessen, Michael D.
ABSTRACT: This article explores the supply of and demand for religiously infused democratic politics in the Muslim majority world. The first half of the article reexamines the widespread support of Muslim publics for both democracy and shari'a law. Results from 15 years of public opinion polls in the Muslim world highlight a clear pattern of support for pious political candidates, but not clerical control of politics. These results, the article further claims, are consistent with contemporary scholars' understanding of Muslim democracy. The second half of the article formulates and then tests several hypotheses about the role of states' religious policies in generating this public demand for Muslim democracy. Using cross-national data on religion-state arrangements and Arab Barometer and World Values Survey data, the article finds support for the hypothesis that religious favouritism increases demand for pious political candidates, but less support for the hypothesis that religious regulation reduces demand for clerical control of politics.